Internalisasi Nilai-nilai Karakter dalam Meningkatkan Kompetensi Kepribadian Guru di SMP Ibrahimy 1 Sukorejo Situbondo - Manan , Muhamad Abdul (Program Pascasarjana Universitas Ibrahimy, 2018)
Undang-undang No. 20 th2003 (Sisdiknas, Chapter 3) national education serves to develop the ability to form character and developing era nation dignity in the framework of the intellectual life of the nation that aimed to develop of potential participants students in order to become human of faith and pious to God Almighty, noble moral, healthy, intellectual, excellence, creative, independent and become citizens of a democratic and responsible. Mandate of the act is one of the basic that should be done. Some of the characters make up at junior high school of Ibrahimy 1 Sukorejo at Situbondo, a stable, mature personality, discipline, wisdom, authoritative, model for learners and the noble moral. As for the process of internalization are through Coaching and conditioning routine, reward, punishment, rules of the Foundation, Call (persuasive), and the creation of an atmosphere of Islamic (religious).